The current status, trends, and challenges of Alzheimer’s disease and other dementias in Asia (1990–2036) - Ziyang He; Ziyang He; Haoqin Zhang; Haoqin Zhang; Guishan Hu; Yinan Qiao; Can Yin; Jianqiao Li; Hong Lin; Anguo Wu; Dalian Qin; Betty Yuen-Kwan Law; et al. (Frontiers in Public Health)
BackgroundWith global aging, Alzheimer’s disease (AD) and other dementias have emerged as significant health threats to the older adults, garnering considerable attention due to their impact on public health. Despite the substantial burden of dementia in Asia, targeted research remains limited. This study aims to assess the current burden, future trends, risk factors, and inequalities in Asia.MethodThe GBD 2021 study was utilized to evaluate the numbers and age-standardized rates (ASRs) of prevalence, mortality, and disability-adjusted life-years (DALYs) of AD and other dementias from 1990 to 2021. Joinpoint regression analysis was performed to assess the trends during this period, while the Autoregressive Integrated Moving Average (ARIMA) model was employed to predict future trends. Additionally, the relationship between disease burden and sociodemographic index (SDI) was also analyzed.ResultsIn 2021, Asia experienced a 250.44% increase in prevalent cases, a 297.34% rise in mortality, and a 249.54% surge in DALYs for AD and other dementias compared to 1990. Meanwhile, the age-standardized prevalence rate, age-standardized mortality rate, and age-standardized DALY rate also exhibited varying degrees of rise from 1990 to 2021. Demographically, the disease burden was higher in women and those aged 65 and above. Regionally, the burden was highest in East Asia and relatively low in South and Central Asia. Nationally, China, India, Japan, and Indonesia reported the most cases. Over the next 15 years, the age-standardized prevalence rate in Asia is expected to peak in 2028 before declining, while the age-standardized mortality rate is anticipated to keep rising. An overall “V” shaped association was found between sociodemographic index (SDI) and the age-standardized DALY rate in Asia. Only smoking, high fasting plasma glucose (FPG), and high BMI were identified as causal risk factors within the GBD framework.ConclusionThe burden of AD and other dementias in Asia has significantly increased over the past three decades and is expected to persistently impact Asian populations, particularly in developing countries experiencing rapid demographic shifts. Women and the older adult should be a focus of attention. It is imperative to implement targeted prevention and intervention strategies, enhance chronic disease management, and control risk factors.